2019
DOI: 10.1111/1759-7714.12977
|View full text |Cite
|
Sign up to set email alerts
|

Management of anlotinib‐related adverse events in patients with advanced non‐small cell lung cancer: Experiences in ALTER‐0303

Abstract: Background Anlotinib is an oral tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor, fibroblast growth factor receptor, platelet‐derived growth factor receptor, and stem cell factor receptor (c‐Kit). In the phase III ALTER‐0303 trial (Clinical Trial Registry ID: NCT 02388919), anlotinib significantly improved overall survival versus placebo in advanced non‐small cell lung cancer patients who had received at least two previous chemotherapy and epidermal growth factor rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 17 publications
(29 reference statements)
7
43
1
1
Order By: Relevance
“…First, blood pressure (BP) assessment is required for patients who are normotensive or hypertensive, and BP should be controlled before treatment is initiated (76,77). Frequent monitoring of BP during the first few months (weekly during the first cycle and subsequently every 2 to 3 weeks) is important for early intervention and the resolution of hypertension.…”
Section: Management Of Drug-associated Aesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, blood pressure (BP) assessment is required for patients who are normotensive or hypertensive, and BP should be controlled before treatment is initiated (76,77). Frequent monitoring of BP during the first few months (weekly during the first cycle and subsequently every 2 to 3 weeks) is important for early intervention and the resolution of hypertension.…”
Section: Management Of Drug-associated Aesmentioning
confidence: 99%
“…In addition, anti-hypertensive drugs (76,78), such as thiazide-type diuretics, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), beta blockers and calcium channel blockers (CCBs), are all suitable choices for patients who develop hypertension during treatment. These drugs may be used alone or in combination, but the combination of ACEIs and ARBs is not recommended.…”
Section: Management Of Drug-associated Aesmentioning
confidence: 99%
“…Most advanced NSCLC patients inevitably have disease progression after rst-line and second-line treatment, and need further treatment. A Phase III clinical study (ALTER-0303) [15] showed that The median OS(9.63 vs 6.3 months,P = 0.0018), PFS 5.37vs1.4 months P < 0.0001 , DCR 81.0% vs 37.1% P < 0.0001 and ORR 9% vs 1% P < 0.0001 of anlotinib were signi cantly better than those of placebo group, and the adverse reactions were generally tolerable, similar to those reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have further identi ed that anlotinib has broader and more effective anti-tumor effects in vivo than Sunitinib and Sorafenib [11][12]13] . Moreover, pre-Phase II and Phase III clinical studies had preliminarily validated the e cacy and safety of anlotinib in the treatment of advanced NSCLC [14][15] .…”
Section: Backgroudmentioning
confidence: 99%
“…5 Anlotinib is an orally available, highly potent multitargeting protein-kinase inhibitor that could block the activation of some receptor tyrosine protein kinase (RTKs), eg, VEGFR2 (vascular endothelial growth factor receptor 2), platelet-derived growth factor receptors α/β (PDGFR α/β), Ret, c-Kit, c-FMS, or discoidin domain receptor 1 (DDR1). 6,7 It has been reported that anlotinib revealed an antitumor effect when used in clinical trials in a variety of human solid tumors, for example nonsmall-cell lung cancer (NSCLC), hepatocarcinoma (HCC), gastric cancer, renal carcinoma (RC), or soft tissue sarcoma. [8][9][10] In 2018, anlotinib was approved by the China Food and Drug Administration (CFDA) for the clinical application of NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%